(untitled) (The Agriculturists, 2015)
A study was conducted at the research farm of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh during August 2011 to May 2012 in two consecutive rice seasons of T. aman and Boro using three types of organic residues viz. poultry manure, cowdung and rice straw as treatments to quantify their effects on soil carbon, nitrogen, carbon sequestration and CO2 emission. Poultry manure was found efficient to increase carbon and nitrogen contents in soils compared to rice straw and cowdung, which decreased with increased soil depths irrespective of residues. Rice straw released more CO2 compared to poultry manure and cowdung. However, a positive trend of carbon enrichment in soils was found with the application these residues. The carbon sequestration in soils under poultry manure was 1.46 t ha-1, while it was 1.26 and 1.19 t ha-1 in cowdung and rice straw, respectively. Application of poultry manure and cowdung in soils should be considered and recommended to increase carbon stock and fetch multiple benefits in agriculture. The Agriculturists 2014; 12(2) 48-55